Pengembangan Situs Web Kampung Ulos Hutaraja - Situmeang, Ruth Putri Agustina; Indah Aini (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
This study aims to develop an informative website to promote Kampung Ulos Hutaraja as a tourist destination. The background of this study is the lack of comprehensive information about Kampung Ulos Hutaraja on tourism websites, especially in German. The method used is the Richey and Klein development model, which consists of three stages: planning, production, and evaluation. The planning stage was carried out through observation of similar websites and direct visits to Kampung Ulos Hutaraja. In addition, interviews were also conducted with the management of Kampung Ulos Hutaraja, which emphasised the importance of digital information media to support foreign tourists. In the production stage, the website was developed using WordPress and provided in Indonesian and German. The results of the evaluation through material validation and media validation showed that the website scored 95 in the ‘very good’ category for material, while in terms of media it scored 94, which is also in the ‘very good’ category. Thus, the Kampung Ulos Hutaraja website is categorised as a suitable information medium for tourism purposes.